Seasonality of antimicrobial resistance rates in respiratory bacteria: A systematic review and meta-analysis - Martinez, Evelyn Pamela; Cepeda, Magda; Jovanoska, Marija; Bramer, Wichor M.; Schoufour, Josje; Glisic, Marija; Verbon, Annelies; Franco, Oscar H. (PloS one, 2019)
Antimicrobial resistance (AMR) rates may display seasonal variation. However, it is not clear whether this seasonality is influenced by the seasonal variation of infectious diseases, geographical region or differences in antibiotic prescription patterns. Therefore, we assessed the seasonality of AMR rates in respiratory bacteria. Seven electronic databases (Embase.com, Medline Ovid, Cochrane CENTRAL, Web of Science, Core Collection, Biosis Ovid, and Google Scholar), were searched for relevant studies from inception to Jun 25th, 2019. Studies describing resistance rates of Streptococcus pneumoniae and Haemophilus influenzae were included in this review. By using random-effects meta-analysis, pooled odd ratios of seasonal AMR rates were calculated using winter as the reference group. Pooled odd ratios were obtained by antibiotic class and geographical region. We included 13 studies, of which 7 were meta-analyzed. Few studies were done in H. influenzae, thus this was not quantitively analyzed. AMR rates of S. pneumoniae to penicillins were lower in other seasons than in winter with pooled OR = 0.71; 95% CI = 0.65-0.77; I2 = 0.0%, and to all antibiotics with pooled OR = 0.68; 95% CI = 0.60-0.76; I2 = 14.4%. Irrespective of geographical region, the seasonality of AMR rates in S. pneumoniae remained the same. The seasonality of AMR rates could result from the seasonality of infectious diseases and its accompanied antibiotic use.